PENGEMBANGAN BUKU AJAR MIKROBIOLOGI SEBAGAI SUMBER BELAJAR MATA KULIAH MIKROBIOLOGI UMUM UNTUK MAHASISWA JURUSAN PENDIDIKAN BIOLOGI UNIVERSITAS BORNEO TARAKAN - Fitri Wijarini (Biopedagogia, 2020)
This study aimed to determine the feasibility of a microbiology textbook as a learning resource for general microbiology courses. The type of research used is development research, according to Borg and Gall. The data collection instrument was a questionnaire. The assessment of the product developed was assessed by two content experts and two lecturers. The designated material experts are lecturers who are competent in the field of microbiology. Meanwhile, the designated practitioners are lecturers who are teaching general microbiology courses. Based on the research assessment results by material expert validators, the value is 84.75% and is categorized as very valid. In comparison, the assessment by practitioners obtained a value of 86.5%, with a very valid category. Keywords: Microbiology, Textbook